Al-HIKMAH AL-MUTA’ALIYAH MULLA SHADRA (KAJIAN EPISTEMOLOGIS) - Laily Nur Arifa (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2017)
After the advent of Peripatetic philosophy (wisdom al-masysya'i) and philosophy iluminasionis(wisdomisyroqi),comes a new school of philosophy who was born in Persia, known as transcendental philosophy (the philosophy of being /wisdomal-muta'aliyah). Hikmah al-muta'aliyah carried by Mulla Shadra, the synthesis of the two previous flow, and iluminasionis Peripatetic philosophy. In the matter of ontology, al-al-muta'aliyah wisdom has given a new breakthrough, with the concept of ashalah al-piece and tasykik al-being. However, the most interesting of the al-al-muta'aliyah wisdom is the aspect of epistemology. al-Hikmah muta'aliyah al-Sadrais a synthesis of intellectual illumination(ishraq),reasoning and rational proof ('aql, burhan or istidlal)as well as religion and revelation(shar').Sadra found perfect knowledge is rational knowledge, combined with spiritual experience can be achieved by those who follow the text of the Koran and Hadith. Source of knowledge is the text of the Koran, Hadith and sayings of the priests, which combined with the experience of intuition and reasoning. In obtaining the knowledge, the most appropriate method is kashf supported by reason and interpret religious texts. For Sadra, science is divided into two major groups, namely hudhuri and husuli. Sadra al-al-muta'aliyah-hiswisdom, is considered a major contribution to Islamic philosophy, Islamic philosophy on delivering the highest peak, which combines bayani, Irfani and Burhani in his analysis.